An assessment of the role of household empowerment in alleviating poverty in Southern Punjab, Pakistan - ul haq, Muhammad Abrar (2017)
Despite successive welfare and anti-poverty programs by the Government of Pakistan, the problems of poverty still persist. The current research aimed to measure household empowerment and analyze its impact to alleviate the incidence of poverty and participatory poverty among the rural households. This study developed a household empowerment index which aimed to obtain first-hand knowledge about the state of household empowerment as measured by the rural household survey. The study also aimed to encourage debates on the measurement of household empowerment besides highlighting the particular dimensions and sub-dimensions of the household empowerment index. The data was collected through multi-stage cluster sampling from the rural households of twenty-four villages in southern Punjab, Pakistan. A total number of 600 households were selected as the sample. The information was gathered through face-to-face interviews of the household heads. The household empowerment index was measured by using three main pillars, namely economic empowerment, social empowerment and political empowerment. These pillars were further divided into forty-two indicators (items) grouped in ten sub-pillars. The weights among the indicators, sub-pillars and pillars of the household empowerment index were obtained by using principle component analysis. The Binary logit model was used to analyze the impact of household empowerment on other control variables on the incidence of poverty. Furthermore, the ordered logit model was used to examine the impact of household empowerment on the participatory poverty of the household. The key findings of this study indicate that the household empowerment index, agriculture occupation, agriculture experience, remittances, female-male ratio, household size, and secondary occupation have inverse relationships with the incidence of poverty and participatory poverty. Therefore, based on the findings ofthis study, it is suggested that poverty may be reduced by improving household empowerment in the said area of southern Punjab, Pakistan.